Integrated Reporting: a bibliometric analysis - Ramlee, Roslida; Mohd Noor, Marjan; Ramlee, Roslily; Awang, Juliana (Universiti Teknologi MARA, Perlis, 2025)
Integrated Reporting has emerged as a comprehensive approach to corporate communication, offering stakeholders a holistic view of an organisation’s performance and creating value across financial and non-financial dimensions. This article presents a bibliometric study on IR using the Scopus database, explores the global trends, major contributors, document types, and subject areas related to IR publications. Findings revealed that scholarly interest in IR has increased following the release of the International Integrated Reporting Framework by the International Integrated Reporting Council (IIRC) in 2013 and later superseded by 2021 framework. Article dominated the document types indicating the field’s academic robustness, with social sciences, business and economics representing the most active subject areas. Macquarie University and the University of Witwatersrand emerged as leading affiliations, while authors such as Maroun, W., and de Villers, C., were among the most prolific contributors. The global trend highlighted South Africa’s pioneering role in IR adoption, alongside notable engagement from Australia, Europe and the United Kingdom. This study underscores the interdisciplinary nature of IR research and its increasing significance in promoting transparency, sustainability, and long-term value creation.